Citizenship, Family Law, and the Repatriation of Islamic State Affiliates in MENA - Trisko-Darden, Jessica (Terrorism and political violence, 2024)
Since the fall of Islamic State’s so-called caliphate in March 2019, the United States and other international actors have repeatedly urged states to repatriate their citizens. Analyses of this issue too often focus on citizens of Western countries despite the fact that they constitute only a small fraction of the group’s members and affiliates. Focusing on Middle East and North African (MENA) countries, we contend that citizenship law and family law play a central role in determining an individual’s prospects for repatriation by forming the basis of a state’s articulation of who belongs to the nation and who the state is responsible for. We identify important sub-regional patterns that shape the repatriation of Islamic State affiliates through the differential treatment of women in MENA citizenship and nationality law and family law. In addition, we find that the distinction between custodian and guardian in MENA family law provides a useful basis for the related challenge of reintegrating female-headed family units as well as orphaned children.